General estimates of the energy cost of walking in people with different levels and causes of lower-limb amputation: a systematic review and meta-analysis. Issue 5 (16th October 2021) - Ettema, Sanne; Kal, Elmar; Houdijk, Han
Abstract : Background: Energy cost of walking (ECw) is an important determinant of walking ability in people with a lower-limb amputation. Large variety in estimates of ECw has been reported, likely because of the heterogeneity of this population in terms of level and cause of amputation and walking speed. Objectives: To assess (1) differences in ECw between people with and without a lower-limb amputation, and between people with different levels and causes of amputation, and (2) the association between ECw and walking speed. Study design: Systematic review and meta-analysis. Methods: We included studies that compared ECw in people with and without a lower-limb amputation. A meta-analysis was done to compare ECw between both groups, and between different levels and causes of amputation. A second analysis investigated the association between self-selected walking speed and ECw in people with an amputation. Results: Out of 526 identified articles, 25 were included in the meta-analysis and an additional 30 in the walking speed analysis. Overall, people with a lower-limb amputation have significantly higher ECw compared to people without an amputation. People with vascular transfemoral amputations showed the greatest difference (+102%) in ECw. The smallest difference (+12%) was found for people with nonvascular transtibial amputations. Slower self-selected walking speed was associated with substantial increases in ECw. Conclusion: This study provides general estimates on the ECw in people with a lower-limb amputation, quantifying the differences as a function of level and cause of amputation, as well as the relationship with walking speed.